Hubungan Status Gizi Berdasarkan Indeks Massa Tubuh Dengan Kadar Hemoglobin Sebagai Determinan Kesehatan Remaja Putri - Putri Permata Sari; Buntar Handayani; Elfira Awalia Rahmawati; Sri Atun Wahyuningsih (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Anemia among adolescent girls remains a significant public health challenge with multifaceted consequences, including impaired growth, reduced academic performance, and compromised future reproductive health. Nutritional status, commonly assessed using Body Mass Index (BMI), is hypothesized to influence hemoglobin levels through various physiological mechanisms, yet the nature and strength of this relationship in specific populations require further investigation. Objective: This study aimed to analyze the relationship between Body Mass Index (BMI) and hemoglobin levels as a determinant of reproductive health among adolescent girls in an urban vocational high school setting. Methods: An analytical observational study with a cross-sectional design was conducted involving 135 adolescent girls selected through total sampling technique. Nutritional status was assessed through anthropometric measurements (body weight and height) to calculate BMI, categorized using Asian-specific cutoffs. Hemoglobin levels were measured using a digital hemoglobinometer. Data analysis employed descriptive statistics for univariate analysis, Spearman correlation test to examine the association between BMI and hemoglobin levels, and Chi-square test to determine the relationship between BMI categories and anemia prevalence, with statistical significance set at p<0.05. Results: The mean age of participants was 17.04±0.76 years, with mean BMI of 23.60±5.90 kg/m² and mean hemoglobin level of 13.11±2.11 g/dL. The majority of participants had normal nutritional status (45.2%), while the prevalence of anemia was 28.9%. Spearman correlation analysis revealed a significant positive correlation between BMI and hemoglobin levels (r=0.285; p=0.001). Chi-square analysis demonstrated a significant association between BMI categories and anemia (χ²=31.65; p<0.001), with the highest anemia prevalence observed among underweight participants (67.9%). Multivariate logistic regression confirmed underweight nutritional status as an independent determinant of anemia (adjusted OR=8.42; 95% CI: 3.12–22.71; p<0.001) after controlling for age, grade, and iron supplementation adherence. Conclusion: This study demonstrates a significant association between BMI and hemoglobin levels among adolescent girls, with better nutritional status correlated with higher hemoglobin levels and lower anemia risk. The findings underscore the importance of integrating routine nutritional assessment and hemoglobin screening into school-based adolescent reproductive health programs. Targeted interventions addressing both underweight and overweight nutritional status, alongside iron supplementation and nutritional education, are essential for comprehensive anemia prevention and improved reproductive health outcomes in this vulnerable population.